2020
DOI: 10.1097/pas.0000000000001506
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MHC Class I Expression in HPV-associated Cervical and Vulvar Neoplasia

Abstract: Tumor cell expression of major histocompatibility complex (MHC) class I is required for antigen presentation and adaptive immune recognition. Absent or diminished MHC class I expression is thought to contribute to immunotherapeutic resistance in some epithelial tumors but has not been previously studied in cervical and vulvar carcinoma. Given that anti–programmed cell death 1 (PD-1) checkpoint inhibition is deployed for programmed cell death ligand 1 (PD-L1)-positive recurrent and metastatic cervical squamous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Studies using IHC and RNA-seq have identified correlations between MHC class II expression on tumor cells and disease-free progression with a positive response to immunotherapies such as anti-PD-1 [ 67 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Furthermore, loss of MHC class I expression has been suggested as a predictor for the development of resistance to immune checkpoint inhibitor therapies in HPV−associated CC, as well as other cancers [ 105 , 106 , 107 , 108 ]. As these therapies rely on CTLs and the expression of immune checkpoint markers, which are upregulated through inflammatory signaling, the observed differences between HPV+ and HPV− CC, as well as subtle differences between HPV α9 and α7 CC, suggest that these tumors may not respond equally to immune checkpoint inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using IHC and RNA-seq have identified correlations between MHC class II expression on tumor cells and disease-free progression with a positive response to immunotherapies such as anti-PD-1 [ 67 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Furthermore, loss of MHC class I expression has been suggested as a predictor for the development of resistance to immune checkpoint inhibitor therapies in HPV−associated CC, as well as other cancers [ 105 , 106 , 107 , 108 ]. As these therapies rely on CTLs and the expression of immune checkpoint markers, which are upregulated through inflammatory signaling, the observed differences between HPV+ and HPV− CC, as well as subtle differences between HPV α9 and α7 CC, suggest that these tumors may not respond equally to immune checkpoint inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that 39.3% to 47.4% of the PD-L1 + OCCC cases using TPS or CPS showed loss of MHC class I expression, consistent with previous studies in various cancer types. [11][12][13][14][15][16] These results suggest that loss of MHC class I expression may contribute to resistance to anti-PD-1/PD-L1 therapies and may also explain the lack of association between PD-L1 positivity (defined as TPS ≥ 1%) and efficacy of nivolumab in the NINJA study. 21 PD-L1 expression and CD8 + TILs have complex relationships and prognostic value in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Together, immunosurveillance is hampered. MHC/HLA I loss is commonly seen in cancers and responsible for unsatisfactory clinical outcomes, because it not only enables cancers to escape immune destruction, but also endows malignant tumor cells, such as breast cancer 50 , endometrial carcinoma 45 , HPV-associated cervical, and vulvar neoplasia 51 , etc., with resistance to immune checkpoint therapies 47 . However, although a vast diversity of molecular mechanisms are relevant to MHC/HLA I loss and any silence in assembly steps of MHC/HLA I can generate MHC/HLA I loss, certain cancers are considered to share common characterized mechanisms and can be treated precisely 49 .…”
Section: Formation Mechanisms Of Immunosuppressive Tmementioning
confidence: 99%